2007
DOI: 10.1055/s-2007-966198
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes and complications of percutaneous endoscopic gastrostomy

Abstract: PEG placement is an easy and safe procedure, although it is often requested too late. No single variable could predict complications or PEG removal. C-reactive protein was found to be predictive of early mortality and Charlson's index was predictive of late mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 16 publications
7
47
0
5
Order By: Relevance
“…The feeding tube can provide palliative decompression too (Pang, 2011). Others believe that the gastrostomy tube should be established early, not late (Figueiredo et al, 2007). For them, the twin-stoma gastrostomy (or 3G tube) should help their cause.…”
Section: The Road Aheadmentioning
confidence: 99%
“…The feeding tube can provide palliative decompression too (Pang, 2011). Others believe that the gastrostomy tube should be established early, not late (Figueiredo et al, 2007). For them, the twin-stoma gastrostomy (or 3G tube) should help their cause.…”
Section: The Road Aheadmentioning
confidence: 99%
“…Die Daten der Literatur und unsere eigenen veranschaulichen, dass die Inzidenz der PEGassoziierten Blutung mit 0-2,5% generell ein seltenes Ereignis ist [8,16]. Unter der Annahme eines 10fach erhöhten Blutungsrisikos unter Antikoagulation ergebe sich eine Fallzahlberechnung von 573 für jede Gruppe (90% Power, α 0,5), mit exponentiellem Anstieg unter der Voraussetzung eines geringeren Risikos.…”
Section: Diskussionunclassified
“…Allerdings lag unserem Studiendesign diese Fragestellung nicht zugrunde. Eine Reduktion äußerer Sterilitätskriterien durch die Verwendung nicht steriler Handschuhe vereinfacht das per se unsterile Verfahren und zeigt sich bei einer Infektrate von 6,6% im Konsens mit der Literatur und für den Patienten ohne beeinträchtigende Folgen [4,8]. Hierbei ist jedoch zu bedenken, ob Tumorpatienten, die mit einer deutlich höheren Infektionsrate belastet sind [7], von einer Antibiotikaprophylaxe und einer Arbeitsweise mit verschärften Sterilitätskriterien nicht erheblich profitieren könnten.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…A similar but prospective study of 168 patients who had PEG tube placement showed a 6.5% 30-day mortality, and C-reactive protein was the only predictive factor for early deaths. Importantly, no single variable could predict either major or minor complications [12]. Alley et al [13] examined the incidence and significance of post-PEG pneumoperitoneum among 120 intensive care unit (ICU) patients.…”
mentioning
confidence: 99%